Mediasi Perceraian dalam Tinjauan Hukum pada Pengadilan Agama - Yangto, Yangto; Sayehu, Sayehu (IAI Nasional Laa Roiba Bogor, 2025)
As social creatures, humans have the instinct to marry and produce new offspring. If there is marriage, the word “marriage” must be associated with divorce. It is interesting to study how the parties to a divorce in the Religious Court make an effort to reconcile or mediate before referring to the verdict. What are the legal consequences of divorce? That is the main issue. And how does the Religious Court handle the divorce mediation process? Marriage is a physical and mental bond between a woman and a man with the aim of building a good, harmonious, and prosperous household. In a marriage, divorce is an unavoidable part. Before the Religious Court decides to divorce, the parties must first conduct a peace process, which is called a mediation process. The purpose of the mediation process is to reduce tension when the trial begins, and it is hoped that the two parties deciding to divorce will decide to repair their relationship and be able to reconcile.